Evaluation of visual performance and eye movements in patients with blue light-filtering intraocular lenses versus ultraviolet light-filtering intraocular lenses - Liu, Yan; Ren, Xiaotong; Wan, Yu; Yang, Luling; Zhang, Rong; Li, Xuemin (Frontiers in Neuroscience, 2023)
Eye movement plays an important role in visual perception and provides essential visual information for everyday tasks. Our previous study indicated that eye movement pattern and visual performance was impaired in age-related cataract patients and could be improved after cataract surgery, but the impact of different intraocular lens (IOL) type was obscure. Previous studies found blue light might affect eye movement pattern and cognitive function. In this study, we explored eye movements and visual performance in post cataract surgery patients implanted with blue light-filtering IOLs or ultraviolet (UV) light-filtering IOLs, to further understand the impact of different types of IOLs on eye movement pattern and daily visual performance, to help ophthalmologists and patients make personalized option of IOL type in the future. Methods Patients after both-eye cataract surgeries were included in this study. Eye movement behaviors were automatically recorded by an eye tracker during performing three performance-based everyday tasks (non-social object search, face recognition and reading). Visual performance and eye movement parameters were compared between participants with blue light-filtering IOLs and UV light-filtering IOLs. The correlation of visual performance and eye movement parameters was explored to determine which eye movement parameters had significant influence on visual performance outcomes.A total of 30 patients (16 with blue light-filtering IOLs and 14 with UV light-filtering IOLs) were included. In this study, we found eye movement pattern was slightly different with these 2 IOLs: During non-social objects visual search task, time to first fixation and fixation counts before first fixation was notably increased in yellow-tinted blue light-filtering IOLs patients. And during reading task, more total fixation count was also found in blue light-filtering IOLs patients. However, the visual performance of these 2 IOLs were close, except for a quicker search of target object with clear UV light-filtering IOLs.Both blue light-filtering and UV light-filtering IOLs are able to successfully restore visual function and yield satisfactory outcomes after cataract surgery. Although subtle, yellow tinted IOLs did have a slight but significant impact on the eye movement pattern and visual performance in elderly patients when handling everyday tasks.